Comportamento ingestivo de vacas leiteiras alimentadas com silagem de milheto ou milho - Rego, Anibal Coutinho do; Oliveira, Mauro Dal Secco de [UNESP]; Signoretti, Ricardo Dias; Dib, Vanessa; Souza Almeida, Geraldo Benedito de (Univ Federal Uberlandia, 2014)
The objective of this study was to evaluate the ingestive behavior of dairy cows fed corn and millet silage with a 5 mm particle size without inoculant, millet silage with a 5 mm particle size with inoculant, millet silage with a 20 mm particle size without inoculant, millet silage with a 20 mm particle size with inoculant. Five cows Holstein x Gir, with approximately 100 days of lactation at the beginning of the experiment and a mean body weight of 550 kg, producing an average of 15 kg of milk per day were used. The animals were arranged in a randomized 5 x 5 Latin square. The total feeding time, rumination time, chewing time, number of alimentary bolus, rumination time for bolus and number of chews was determined. The variables that make up the feeding behavior were not affected when the cows were fed different millet silages compared with corn silage. Cows fed corn silage and millet silage of 5 mm particle size had a higher intake of dry matter and neutral detergent fiber. A particle size between 5 and 20 mm, the presence or absence of inoculum and the type of silage with DM at 28%, does not affect the total feeding time, ruminating and resting of cows with an average production of 15.2 kg per day. The presence of the inoculant does not affect the intake of dry matter and neutral detergent fiber. Cows fed diets containing corn silage or pearl millet silage with a 5 mm particle size fed more DM.

Objetivou-se com este estudo avaliar o comportamento ingestivo de vacas leiteiras alimentadas com dietas contendo como volumoso silagem de milho ou silagem de milheto com 5 ou 20 mm de tamanho de partículas, com ou sem inoculante bacteriano. Foram utilizadas cinco vacas mestiças Holandês × Gir, com aproximadamente 100 dias de lactação ao início do experimento e peso corporal aproximado de 550 kg, produzindo, em média, 15,2 ± 2,3 kg de leite por dia. Os animais foram arranjados num delineamento em quadrado latino 5×5. O tempo total de alimentação, ruminação e ócio, não foi alterado pelo tipo de silagem na dieta. As variáveis que compõem o comportamento ingestivo não foram afetadas quando as vacas receberam as diferentes silagens de milheto comparadas com silagem de milho. O tamanho de partículas entre 5 e 20 mm, a presença ou não de inoculante e o tipo de silagem com teores de MS em 28%, não afeta o tempo total de alimentação, ruminação e ócio em vacas mestiças Holandês Gir com média de produção de 15,2 kg por dia. Silagem de milho ou milheto, tamanho de partículas 5 ou 20 mm, e o uso ou não de inoculante em silagem de milheto, não altera o tempo total despendido com alimentação, ruminação e ócio em dietas para vacas leiteiras mestiças Holandês × Gir com média de produção de 15,2 kg por dia.
Ingestive behavior of dairy cattle fed millet and corn silage
Keywords: inoculants; Lactobacillus plantarum; Particle size, Pennisetum glaucum (L.) R. B.; Propionibacterium acidipropionici